Treating alcoholism : helping your clients find the road to recovery - Perkinson, Robert R. (John Wiley & Sons, 2004)
Help your clients find the path to overcoming their addiction Alcoholics are one of the most difficult client groups to treat effectively. To preserve their way of life, they may lie about their problem or deny that one exists; that is the nature of this profoundly powerful disease. Yet if you can guide each of your clients through their own resistance towards the truth, not only will you be rewarded with starting them on the road to recovery, you will no doubt have saved their life as well. Achieving such a victory goes to the heart of being an addiction counselor; it is the experience of healing on a direct and tangible level. Treating Alcoholism provides a complete road map for assessing, diagnosing, and treating this multifaceted and tenacious illness. Detailed clinical information on the disease accompanies ready-to-use tools for practice. With a special emphasis on the 12 Steps of Alcoholics Anonymous, the author walks you through the first five steps of this established methodology in comprehensive detail, showing how to easily apply each one to treatment. Other useful resources in Treating Alcoholism include: * A sample treatment plan * Copies of alcohol screening tests (SMAST and CAGE questionnaires) * Tests for other potentially related problems such as gambling and sexual addiction * A sample behavioral contract for use with adolescents * Listings of additional resources The treatment of alcoholism is fraught with struggles and hazards for both client and caregiver. Written in a lively tone that resonates with the author's compassion for his own clients, Treating Alcoholism gives you reliable, up-to-date, and practice-tested information and materials you need to successfully confront this deadly disease and start your clients on the path to recovery.